Corruption and Nigeria’s External Image in the Fourth Republic (Journal of Management and Social Sciences, 2020)
The existence of corruption is not new in the governance of countries. It is both a national and international menace with multidimensional effects thereby evoking national and supra-national efforts towards combating it. In Nigeria, it has led to institutionalisation of the fight against corruption as evidenced in the establishment of the Independent Corrupt Practices and other Related Offences Commission (ICPC) and the Economic and Financial Crimes Commission (EFCC). However, due to some factors in the fight against corruption, the effect it has on governance has continued. One area of significance is the effect it has on the country’s external image. This underscores the link between domestic politics and external relations. It is against this background that this paper examines the impact of corruption on Nigeria’s external image in the Fourth Republic. By focussing on specific cases that have generated international reactions, the paper argues that though the fight against corruption is within the purview of Nigeria’s domestic policy, the nature and outcome of such endeavour has implications for how the country in the comity of nations. It, therefore, recommends that domestic policies must not be unmindful of the likely consequences of such policy on a country’s external relations.